EAD505 : Introduction to visual culture / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
Visual Culture aims to introduce students to all aspects of culture that communicate through visual means within fine art or non-fine art disciplines. This course focuses on aspects of culture that rely on visual images as well as visual objects and their influences on society.